The Effectiveness of gamestolearnenglish.com on Vocabulary Mastery of The Fourth Grade SDN 4 Tamansari in The Academic Year 2023/2024 - Lailatul Maftuha; Novelin Putri Yanuar; Biaggi Banidhar Jodhi; Iva Nuria Indah; Nur Hasibin (MAN Insan Cendekia Jambi, 2025)
Teaching vocabulary through games has gained recognition as an engaging and effective approach to improve and enhance students' word knowledge and retention. Based on preliminary study in SDN 4 Tamansari, the students have problem with their vocabulary. This research aims to measure whether there is a significant effect of gamestolearnEnglish website on the vocabulary mastery of the fourth grade at SDN 4 Tamansari in the academic year 2023/2024. This research is quantitative research with pre-experimental research design. There are 12 respondents of the fourth grade students at SDN 4 Tamansari. Purposive sampling technique is used to choose the sample in the school. Multiple choice test is chosen for the data collecting method that consist of 30 questions of common noun, adverb of time and verb for the test. For the data analysis, the researcher used t-test formula. The mean score was 46,83 in the pre-test and 78,41 in the post-test. The result of t-test is higher than t-table (8,494 > 2.201). Thus it can be concluded that There is a significant effect of gamestolearnEnglish.com website on the vocabulary mastery of the Fourth grade SDN 4 Tamansari in the academic year 2023/2024